2015
DOI: 10.1007/s10811-014-0492-2
|View full text |Cite
|
Sign up to set email alerts
|

Chlorococcum sp. MM11—a novel phyco-nanofactory for the synthesis of iron nanoparticles

Abstract: Green synthesis of iron nanoparticles using a soil microalga, Chlorococcum sp. MM11, and their application in chromium remediation have been investigated. Sphericalshaped nanoiron was synthesized by treating the exponentially growing culture of Chlorococcum sp. with 0.1 M iron chloride solution for 48 h and incubating it under shaking in the dark. The appearance of a yellowish brown colour indicated the biotransformation of bulk iron into nanoiron. Morphological characteristics of nanoparticles with transmissi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 146 publications
(22 citation statements)
references
References 39 publications
0
19
0
Order By: Relevance
“…X-ray diffraction (XRD) showed that the nanoparticles were crystalline in nature, with a cubic shape. Subramaniyam et al [32] employed soil micro algae, Chlorococcum sp., with an iron chloride precursor to synthesize the spherical-shaped nanoiron ranging in size from 20–50 nm. The surface of microalagl cell contained nanoiron, not only localised inside as well as outside the cell as revealed by TEM.…”
Section: Green Routes For the Synthesis Of Metallic Iron Nanopartimentioning
confidence: 99%
“…X-ray diffraction (XRD) showed that the nanoparticles were crystalline in nature, with a cubic shape. Subramaniyam et al [32] employed soil micro algae, Chlorococcum sp., with an iron chloride precursor to synthesize the spherical-shaped nanoiron ranging in size from 20–50 nm. The surface of microalagl cell contained nanoiron, not only localised inside as well as outside the cell as revealed by TEM.…”
Section: Green Routes For the Synthesis Of Metallic Iron Nanopartimentioning
confidence: 99%
“…This has necessitated research into biological methods involving the development of facile, greener and eco-friendly reducing agents for nanoparticles formation, resulting in the convergence of nanotechnology, environmental remediation and green chemistry. Researchers have reported the use of microorganisms such as bacteria, fungi and algae (Kaul et al, 2012;Subramaniyam et al, 2015), ionic liquids and eutectic solvents (Sanchez et al, 2018), bio-and agrowaste (Nisticò et al, 2018;Yang et al, 2018;Olajire et al, 2017a,b), plant materials such as leaves, fruit (Kumar et al, 2014;Mohan Kumar et al, 2013) and seed (Radini et al, 2018;Venkateswarlu et al, 2014), T microwave heating (Alvarez-romero et al, 2018;Liang et al, 2017;Kombaiah et al, 2018a), and biodegradable polymers as greener routes for the synthesis of various nanoparticles. Other green-based methods for green synthesis of iron nanoparticles reported include amino acids (Marimón-Bolívar and González, 2018), vitamins, enzymes and waste (Wei et al, 2016a).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, Figure 7B presents the characteristic peaks for Fe and the binding energy peaks appearing at 722.5 and 711.9 eV (1 eV = 1.602 × 10 −19 J) represents Fe2p 1/2 and Fe 2p 3/2 respectively. [ 8 ] Additionally, Figure 7C shows the characteristic peaks for chromium adsorbed onto capped iron oxide nanoparticles. On the other hand, the binding energy peaks at 576.2 to 578.5 eV and 588.9 eV corresponds to Cr (III) 2p 3/2 and Cr (VI) 2p 3/2 , respectively.…”
Section: Resultsmentioning
confidence: 99%